Evaluation of blood pressure responses to treadmill exercise test in normotensive children of hypertensive parents - Özdemir, Gökmen; Köşger, Pelin; Uçar, Birsen (The Turkish Journal of Pediatrics, 2020)
Background. Hypertension is a progressive disease with a prehypertensive phase. The most important feature of this period is the abnormal cardiovascular reactivity to various stressors. In our study, we focused on normotensive children of hypertensive parents, a special group that is at risk. Methods. We evaluated the children according to age, studying whether they showed higher cardiovascular reactivity at different steps of an exercise test and during a recovery period than their counterparts with a negative history. A total of 110 normotensive children who were between the ages of 6 and 18 years were enrolled into the study. Sixty-two children whose parent(s) had a history of hypertension formed the study group while 48 without this history formed the control group. An exercise test was performed according to the Bruce protocol. Maximal systolic blood pressures and systolic blood pressures were taken while the participants were at rest; during phases 2 and 3; and also in the first, third, and sixth minutes of the recovery period. Results. Measurements were significantly higher in the study group (p < 0.05). In the group of children between the ages of 6 and 10 years, cardiovascular responses were similar. Children older than 10 years, however, had significantly higher blood pressure levels than those in the control group. The children who were at risk of hypertension showed more exaggerated cardiovascular responses during the exercise test and recovery period. This response was particularly evident for those children 10 years of age and older. Conclusions. Our study indicates that treadmill exercise is a safe and effective investigational method which can be used to identify children who are at risk for development of hypertension before this condition becomes clinically evident.
Keywords: blood pressure; cardiovascular physiological processes; exercise test; risk factors